Cancer therapeutics based on diverse energy sources. (7th September 2022) - Son, Subin; Kim, Jungryun; Kim, Jaewon; Kim, Byungkook; Lee, Jieun; Kim, Yuri; Li, Mingle; Kang, Heemin; Kim, Jong Seung
Abstract : Light has been utilized for cancer treatment owing to its advantages. Low penetration depth of light restricts its application in cancer treatment. To overcome the drawback, various treatments based on each energy sources have been developed. Abstract : Light-based phototherapy has been developed for cancer treatment owing to its non-invasiveness and spatiotemporal control. Despite the unique merits of phototherapy, one critical disadvantage of light is its limited penetration depth, which restricts its application in cancer treatment. Although many researchers have developed various strategies to deliver light into deep-seated tumors with two-photon and near-infrared light irradiation, phototherapy encounters the peculiar limitations of light. In addition, high oxygen dependency is another limitation of photodynamic therapy to treat hypoxic tumors. To overcome the drawbacks of conventional treatments, various energy sources have been developed for cancer treatment. Generally, most energy sources, such as ultrasound, chemiluminescence, radiation, microwave, electricity, and magnetic field, are relatively free from the restraint of penetration depth. Combining other strategies or therapies with other energy-source-based therapies improves the strength and compensates for the weakness. This tutorial review focuses on recent advances in the diverse energy sources utilized in cancer treatment and their future perspectives.